Observation of the efficacy of subcutaneous filling with micro-cross-linked hyaluronic acid for infraorbital rejuvenation - XIE Heng; HUANG Lining (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To assess the efficacy and safety of subcutaneous injection of micro- cross- linked hyaluronic acid (MCLHA) in improving infraorbital aging. [Methods] From March 2022 to June 2023, 37 patients with both tear trough deformity and eye bags were recruited at the Dermatology Hospital of Southern Medical University. The filling treatment plan of MCLHA in the infraorbital region was determined according to the classification of tear trough deformity. After the treatment, the Allergan infraorbital hollowness scale (AIHS) and the global aesthetic improvement scale (GAIS) were used to evaluate the efficacy. Meanwhile, patient self-evaluation of the efficacy and satisfaction, and adverse reactions were recorded. [Results] After the treatment, the improvement rate of AIHS scores was 94.59% (35/37). The improvement rates of GAIS scale by physicians and patient self-evaluation were 100% and 91.89%(34/37), respectively. The patients′ satisfaction rate was 91.89%(34/37). Bruise occurred in 5 patients, and the Tyndall effect was observed in 1 patient. No patient had either postoperative local edema or other complications such as infections, hematoma, allergy, or thrombus. At the 6-month postsurgical follow-up, 35.14% (13/37) of the patients still showed improvement compared to the pretreatment. [Conclusions] Subcutaneous injection of MCLHA is a safe and effective method for improving infraorbital aging, and can be regarded as a non-surgical treatment option for patients with tear trough deformity and lower eyelid bags.